Enhanced Catalytic Performance for H2 Harvesting from Steam Reforming of Methanol Using Glycine Nitrate Process Synthesized Novel CuFeO2–ZnFe2O4 Porous Nanocomposite Catalyst - Chung‐Lun Yu; Subramanian Sakthinathan; Ching‐Lung Chen; Satoshi Kameoka; Naratip Vittayakorn; Hongbing Jia; Te‐Wei Chiu (Langmuir, 2025)
nanocomposite as a cost-effective catalyst for on-demand hydrogen generation in fuel cell applications in the future.
Keywords: Catalytic Processes in Materials Science; Catalysts for Methane Reforming; Copper-based nanomaterials and applications